Factors Affecting the Marketing of organic Farming Products (case Study: Miandoab county) - Zohreh Jesarati (International Journal of Agricultural Management and Development, 2018)
Organic agriculture is rapidly growing while the lack of knowledge and skills to manage organic farms and the lack of market opportunities for the organic products are the most important reasons for the disinclination to the use of the organic agriculture practices. The main aim of this study was to determine the factors underpinning the marketing of organic agriculture products. The research was a descriptive survey in terms of purpose. The research instrument was a questionnaire whose validity was determined by the content validity and its reliability was estimated to be 89% by Cronbach's Alpha. The population of the study included all organic farmers who have supplied their products to a fruit and vegetable market in Miandoab. The sample size was determined as 148 by the Morgan-Kerjisy table and was selected by stratified sampling method and simple randomization. Finally, 150 questionnaires were collected. The results showed a significant relationship between the marketing of the organic agriculture products with educational factors, economic factors, intelligence agents, production factors and social factors at the 0.05 level. Also, the results of regression analysis showed that the variables of production factors, educational factors, and economic factors captured 53% of the variance of the dependent variable.